2016
DOI: 10.5334/irsp.51
|View full text |Cite
|
Sign up to set email alerts
|

The Charlie Hebdo Terror Attack in Paris: Follow-up of French Citizens’ Terrorist Threat Perception and Its Aftermath <br/> [L’attaque Terroriste de Charlie Hebdo à Paris : Evolution temporelle de la Perception de la Menace Terroriste et de ses Conséquences auprès des Citoyens Français]

Abstract: Terrorism is one of the most frightful large-scale societal threats nowadays. The January 7, 2015 Charlie Hebdo terrorist attack in Paris shattered French's sense of security. The present research investigates French citizen's (N = 160) terrorist threat perception (personal vs. collective), behavioral changes, social sharing of emotions and perceived socioemotional climate using the social stage model of collective coping with disasters (Pennebaker & Harber, 1993). This study was conducted by a questionnaire a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 47 publications
(85 reference statements)
2
12
0
Order By: Relevance
“…Both the paper by Cohu, Maisonneuve and Testé (2016) and the one by Pelletier and Drozda-senkowska (2016) show how the use of an extended time frame can be useful. They report evidence based on repeated observations made over time so that one can grasp how things evolved.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Both the paper by Cohu, Maisonneuve and Testé (2016) and the one by Pelletier and Drozda-senkowska (2016) show how the use of an extended time frame can be useful. They report evidence based on repeated observations made over time so that one can grasp how things evolved.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Their posters said "I am Charlie", "I am Jewish", "I am Muslim", "I am a cop", expressing solidarity with the murdered victims and attachment to freedom of expression (see Pelletier & Drozda-Senkowska, 2016). Few weeks later, however, other interpretations of the rallies took over.…”
mentioning
confidence: 99%
“…Finally, the adaptation phase takes place from six weeks onwards and entails a return to low levels of interpersonal sharing of experiences. In line with this model, a similar pattern of social sharing of emotionally charged information has been apparent over a two-month period in post-terrorist contexts (Pelletier & Drozda-Senkowska, 2016;Rimé et al, 2010). Although, temporality might affect also related meaning-making and rumour-mongering processes following a terrorist attack, the scientific literature has rarely explored the temporal perspective (for exceptions, see Bordia & Rosnow, 1998;Murphy, Johnson, & Lohan, 2003;Updegraff et al, 2008).…”
Section: Rumour-mongering In the Context Of Terrorismmentioning
confidence: 56%
“…These different domains relate to basic human needs such as need for self-esteem, certainty, belongingness, and the need for symbolic immortality. Indeed, previous research conducted in post-terrorist contexts showed that laypeople experience greater concern for others, the loved ones especially (Bux & Coyne, 2009), and they also tend to spend more time with their family and friends following the terrorist attack (Goodwin, Willson, & Gaines, 2005;Huddy, Feldman, Capelos, & Provost, 2002;Pelletier & Drozda-Senkowska, 2016). Thus, the human beings' core affiliative tendencies and need for meaningful social bonds (Baumeister & Leary, 1995) could constitute one of the compensatory domains related to the threat of meaning in post-terrorist contexts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation